(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of Agromyzidae, Phytomyza camuna, is described. The larva forms large blotch mines on leaves of Thalictrum aquilegifolium. A key of Phytomyza living on Thalictrum sp. in Europe and in North America is given.